P13-S Brainstem auditory and median somatosensory evoked potentials evaluation of clinical outcome in hemorrhagic stroke patients. Issue 7 (July 2019) - Blazevic, Nikola; Skoric, Magdalena Krbot; Poljaković, Zdravka; Supe, Svjetlana; Matijević, Vesna; Alvir, Domagoj; Bazina, Antonela; Ljevak, Josip; Starčević, Katarina; Jovanović, Ivan; Habek, Mario; Gabelić, Tereza
Abstract : Introduction: Aim of this study was to assess evoked potentials in the prediction of clinical outcome in hemorrhagic stroke patients. Methods: In 46 patients (23 men, mean age 65.17 ± 12.58) with hemorrhagic stroke (33 intracerebral and 13 subarachnoid hemorrhage) within the 48 h after admission to neurointensive care unit (NICU), brainstem auditory evoked potentials (BAEP) and median nerve somatosensory evoked potentials (mSSEP) were performed. Among clinical parameters, the Glasgow Coma Score (GCS) and the Full Outline of Unresponsiveness (FOUR) were assessed on the admission and discharge day, while Modified Rankin scale (mRS) was assessed on the discharge day. Results: At the admission, there was statistically significant negative correlation between BAEP latencies and FOUR score and GCS. Regarding discharge data, there was significant negative correlation between discharge GCS and right wave V latency and significant positive correlation of mRS with latency of right wave V. Among mSSEP results, significant negative correlation was found between right P14-N20 interlatency and admission date FOUR score and GCS. Also, significant positive correlation was found between both FOUR score and GCS on the admission date with mSSEP P15-N20 amplitudes. Significant positive correlation was found between mSSEP P15-N20 amplitudes and discharge day GCS and FOUR scale values. mRS significantly positively correlated with N20 latencies, while significant negative correlation was found between mRS and mSSEP P15-N20 amplitudes. Conclusion: BAEP and mSSEP correlate with different clinical outcomes at admission and discharge in patients with hemorrhagic stroke.